PD-1 is conserved from sharks to humans: new insights into PD-1, PD-L1, PD-L2, and SHP-2 evolution - Kondo, Ryohei; Kondo, Kohei; Nabeshima, Kei; Nishikimi, Akihiko; Ishida, Yasumasa; Shigeoka, Toshiaki; Dijkstra, Johannes M. (Frontiers in Immunology, 2025)
Programmed cell death protein 1 (PD-1) is an immune checkpoint molecule until recently believed to exist only in tetrapod species. However, together with a very recent study dedicated to the CD28/CTLA4 molecule family, this study—using database information—identifies the PD-1 gene in both bony and cartilaginous fish, while being the first to present a detailed molecular analysis of the evolution of PD-1 and its ligands. Conserved sequence motifs imply an ancient origin of PD-1’s binding modes to its extracellular ligand PD-L1 and its intracellular ligand Src homology region 2 domain-containing phosphatase-2 (SHP-2), and also of its N116 glycosylation motif—a less well known PD-1 feature—important for binding galectins. The PD-1 cytoplasmic tail binds SHP-2 by two motifs, defined as an immunoreceptor tyrosine-based inhibitory motif (ITIM) and immunoreceptor tyrosine-based switch motif (ITSM), but sequence conservation patterns show that these definitions warrant a discussion. As in mammals, PD-1 transcripts in fish could be found co-expressed with markers of regulatory and exhausted T cells, suggesting a similar immune checkpoint function. Agreeing with previous reports, the PD-L1/PD-L2 gene duplication was only found in tetrapod species, while we newly discovered that features that consistently distinguish the two molecules are PD-L2 IgC domain motifs. Among PD-L1 (the name given to the single PD-L ancestral molecule) of many ray-finned fish, conservation of a very long cytoplasmic tail motif supports previous claims that PD-L1 cytoplasmic tails may have a function. Surprisingly, we found a gene similar to SHP-2—that we named SHP-2-like (SHP-2L)—to be conserved from sharks to mammals, although lost or inactivated in higher primates and rodents. SHP-2L is expected to bind PD-1 similar to SHP-2. This comparative analysis of PD-1 and its interacting molecules across jawed vertebrates highlights conserved immune checkpoint features while revealing new insights and lineage-specific adaptations.